ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. D DENGAN PERSALINAN PRESIPITATUS DAN PENERAPAN PIJAT LAKTASI MASA NIFAS DI PUSKESMAS CIKANJANG KABUPATEN GARUT - Atifah, Rifa Salsabila; Mulyati, Sri (Politeknik Kesehatan Kemenkes Bandung, 2024)
During the labor process, complications such as partus precipitatus can occur which affect the mother and fetus. In addition, some mothers experience lactation problems, lactation massage is one solution to overcome difficulties in producing breast milk and comprehensive care is one effort to improve the quality of maternal and child health. The purpose of this Final Assignment Report is to implement this comprehensive care to implement comprehensive care.The method in compiling this Final Assignment Report is a case study with comprehensive midwifery management starting from February-March 2024 in the Cikajang Health Center area, Garut Regency. The subject of this care is Mrs. D with a gestation period of 38 weeks, labor, BBL, to 6 weeks of postpartum. Data collection techniques come from primary and secondary data.During the comprehensive care process, problems were found during pregnancy, namely frequent urination at night, which can be overcome by counseling to reduce drinking at night. During labor, there was a precipitous labor for ≥ 3 hours, the baby was born spontaneously and cried immediately, the placenta was born spontaneously and no placental remains were found. During the postpartum period, there was breast congestion and it was felt that breast milk production was low so lactation massage care was given. Lactation massage is done 2 times a day for 15-20 minutes to help increase breast milk production, in newborns who experience jaundice, this problem can be overcome by providing counseling and care as needed.